2018
DOI: 10.1108/sajbs-06-2018-0064
|View full text |Cite
|
Sign up to set email alerts
|

Do Indian stock market sentiments impact contemporaneous returns?

Abstract: Purpose The purpose of this paper is to analyse the impact of Indian investor sentiments on contemporaneous stock returns of Bombay Stock Exchange, National Stock Exchange and various sectoral indices in India by developing a sentiment index. Design/methodology/approach The study uses principal component analysis to develop a sentiment index as a proxy for Indian stock market sentiments over a time frame from April 1996 to January 2017. It uses an exploratory approach to identify relevant proxies in building… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…Verma and Verma (2007) showed that investor sentiment has a positive impact on asset return, but it makes an adverse impact on individual and institutional investors owing to market volatility. Aggarwal and Mohanty (2018) studied the impact of the investor sentiment index on the Indian stock market and found that there is a positive relationship between stock returns and investor sentiments. However, most of these studies focused on the general effect of investors' sentiment on stock returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Verma and Verma (2007) showed that investor sentiment has a positive impact on asset return, but it makes an adverse impact on individual and institutional investors owing to market volatility. Aggarwal and Mohanty (2018) studied the impact of the investor sentiment index on the Indian stock market and found that there is a positive relationship between stock returns and investor sentiments. However, most of these studies focused on the general effect of investors' sentiment on stock returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers over the years have used various direct and indirect proxies to measure sentiment, but there are no universal proxies to measure investor sentiment (Aggarwal and Mohanty, 2018;Chen et al, 2020). Therefore, the first task is to measure the investor sentiment of the Indian investors by constructing an investor sentiment index.…”
Section: Measurement Of Sentimentmentioning
confidence: 99%
“…Investors' irrationality has attracted the attention of academicians and practitioners across the globe. As a result, researchers have increasingly focused on investor sentiment and its relationship with stock returns (Aggarwal & Mohanty, 2018;Al-Nasseri et al, 2021;Baker & Wurgler, 2006;Brown & Cliff, 2004, 2005Canbas & Candir, 2009;Chakraborty & Subramaniam, 2020;Dash & Mahakud, 2012;Rashid et al, 2019;Sayim & Rahman, 2015). However, the studies focusing on the sentimentreturn relationship in the Indian context are limited (Aggarwal and Mohanty, 2018;Chakraborty and Subramaniam, 2020;Mahakud, 2012, 2013;Dash and Maitra, 2018;Pandey and Sehgal, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, according to Bu and Li (2014), the sentiment index is a good predictor of the Chinese stock returns. On the other hand, Aggarwal and Mohanty (2018) investigated the impact of the investor's sentiment index on the Indian stock market and discovered a positive correlation between the stock returns and the investor's sentiment.…”
Section: Introductionmentioning
confidence: 99%